Characterization of sunflower (Helianthus Annuus L.) lines for Alternariaster leaf spot disease resistance: Characterization of sunflower (Helianthus Annuus L.) lines for Alternariaster leaf spot disease resistance - VIKAS V KULKARNI; POORNIMA; VIJAYKUMAR GHANTE; M R UMESH (Journal of Oilseeds Research, 2023)
Leaf spot disease is an important disease of sunflower that reduces the photosynthetic area and causes the yield loss. An investigation was undertaken for screening of breeding lines to Alternariaster leaf spot during Kharif 2021. Among 75 breeding lines including susceptible check KBSH-44 evaluated in augmented block design with two replications at Sunflower Scheme, MARS, Raichur, five lines viz., RSLP-18 (PDI=8), RSLP-22(PDI=8), RSLP98(PDI=7.5), RCB-19-9(PDI=7.5) and PM-160 (PDI=9) with resistant reaction to Alternariaster leaf spot whereas RSLP-89, RSLP-99 and PM7 recorded medium resistance reaction in post-flowering stage.